The Influence of Work Culture on Performance Productivity of Landungsari Village Apparatus, Dau District, Malang Regency - Valensia Bulu; R Y Susanto; Fendiyatmi Kusufa (International Research & Development for Human Beings (IRDH), 2026)
The study aims to directly determine whether there is a significant influence on work culture on employee performance productivity at the Landungsari Village Office, Dau District, Malang Regency. One of the methods or techniques used in collecting data or information is questionnaires, observation and documentation. The population in this study was 50, as used for sampling using the total sampling method, which means that the entire population will be used as a sample, so the conclusion is that the sample used in this study was 50 samples. The data analysis used in this study was using simple linear regression analysis, as assisted by using SPSS 26 Software. The results found in this study were that there was a significant influence on work culture on employee performance productivity at the Landungsari Village Office, Dau District, Malang Regency